2007
DOI: 10.3892/or.18.3.729
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Magnolia officinalis mediates proliferative capacity, p21WAF1 expression and TNF-α-induced NF-κB activity in human urinary bladder cancer 5637 cells; involvement of p38 MAP kinase

Abstract: Abstract. Magnolia officinalis is a commonly used herb in East Asian countries and has multiple pharmacological effects. Although Magnolia officinalis has a variety of pharmacological effects on certain cancer cell types, the molecular mechanisms on urinary bladder cancer are unclear. An aqueous extract of M. officinalis inhibited cell proliferation in cultured human urinary bladder cancer 5637 cells. Inhibition of proliferation was associated with G1 cell cycle arrest. Treatment with M. officinalis extract bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…COLO-205; Hep-G2 Induced Bax, Bak, and Bad; decreased Bcl-xL and mcl-1 protein levels; regressed formed solid tumor with COLO-205 implanted subcutaneously in nude mice [201]; induced G1 cell cycle arrest; inhibited phosphorylation of Akt and Rb, up-regulated PTEN [202][203][204] Retard growth of PC-3 xenografts in nude mice [205] Hydroxyisovaleryls hikonin (beta-HIVS)…”
Section: Panax Ginsengmentioning
confidence: 99%
“…COLO-205; Hep-G2 Induced Bax, Bak, and Bad; decreased Bcl-xL and mcl-1 protein levels; regressed formed solid tumor with COLO-205 implanted subcutaneously in nude mice [201]; induced G1 cell cycle arrest; inhibited phosphorylation of Akt and Rb, up-regulated PTEN [202][203][204] Retard growth of PC-3 xenografts in nude mice [205] Hydroxyisovaleryls hikonin (beta-HIVS)…”
Section: Panax Ginsengmentioning
confidence: 99%
“…M. officinalis cortex is a key ingredient of several traditional medicines such as Pyengwisan and Banhahubaktang that are commercially available and widely prescribed at traditional medicine clinics in Korea 11, 12. Previous studies have shown that M. officinalis extracts have antibacterial, 13 antiatherogenic, 14 antineuroinflammatory, 15 and anticancer effects 16 . Moreover, M. officinalis cortex has several biological active components, including magnolol and honokiol, to have beneficial effects on ligature-induced periodontitis or arthritis by inhibiting osteoclastogenesis, suggesting an inhibitory potential of M. officinalis cortex on inflammatory-induced bone disease 17, 18.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, the short PRLR has the potential to activate Jak2, which is able to further activate the ERK1/2 pathway. In certain cell types, sustained ERK1/2 activation also leads to p21/waf1 upregulation, cell cycle arrest, differentiation and apoptosis (10)(11)(12). In the p21 gene promoter region, there are 2 Stat5 activating sites; however, it is unclear whether S179D PRL upregulates p21/waf1 via Stat5 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Short PRLR signaling may trigger the activation of JNK, c-jun and c-fos, resulting in the activation of activating protein-1 (AP-1) and the upregulation of p21/waf1 in human prostate cancer cells. Previous studies have demonstrated that the accumulation of ERK1/2 resulted in the upregulation of p21 (10)(11)(12). Structurally, the short PRLR has the potential to activate Jak 2 and further activate MAPKs.…”
Section: Introductionmentioning
confidence: 99%